KETERKAITAN INFORMASI AKUNTANSI DAN DUKUNGAN MANAJEMEN PUNCAK TERHADAP KINERJA SISTEM INFORMASI AKUNTANSI - Amir Faisal; Jeremia Permatahati (Ekonomi Digital, 2022)
This study aims to determine the relationship between information technology development, the accounting information system user capabilities, top management support and information quality on the performance of accounting information systems (AIS) in the Jakarta hotel sector. This study examined 45 hotels in the Jakarta area by using a sample population of 100 employees with varied positions and divisions in the hotel business. The research method in this thesis is descriptive statistical analysis, data quality test, classic assumption test, and hypothesis testing. The type of data used is primary data. The independent variables in this study are information technology development, the accounting information system user capabilities, top management support and information quality. The dependent variable is the performance of accounting information systems (AIS). The results of this study prove that the development of information technology has a significant effect on the performance of accounting information systems, the variable ability of accounting information system users does not significantly influence the performance of accounting information systems, top management support variables significantly influence the performance of accounting information systems and information quality variables significantly influence the performance of accounting information systems (AIS).